Definition of Basic Numerical Patterns in the Ranks of the Hryvnia to the US Dollar and Russian Ruble Against the US Dollar Based on the Wavelet Transform - Kachynsky, Anatoly; Tkach, Volodymyr; Bashynsky, Bohdan (Journal of Applied Nonlinear Dynamics, 2026)
The wavelet analysis is a fairly new approach to the study of various systems, especially for financial markets. Wavelet transform is the decomposition of a one-dimensional signal based on a soliton-like function (wavelet) by its stretching (compression) and displacement along the time axis. In a period of a market-driven global economy, when financial crises are significant sources of destabilization of not the economy only, anticipation and minimization of losses from global financial crises are very important. The study of the currency market is one of the pressing problems of the modern economy, which in its turn addresses the mathematical tools. The purpose of the work is to determine the main regularities in the numerical series of the Ukraine hryvnia (UAH) against the US dollar and the Russian ruble (RUR) to the US dollar (USD).